Proposal and effect evaluation of RPC application with energy storage system for regenerative energy utilization of high speed railway. Issue 1 (1st January 2017) - Takagi, Kazunori; Takagi, Masaaki; Hayashiya, Hitoshi; Iwafune, Yumiko
Abstract: All car of Tohoku-Shinkansen is equipped with the regeneration brake. This car is returning electric power to the Catenary line when it is braking. Regenerative power can improve the energy efficiency if other cars can use regenerative power. But the regenerative power flows back to the grid via the traction substation when other train does not exist in the same section. At this time, the regenerative power flowing back is not metered. This study is to measure the regenerative energy that flows back to the grid. We need determine the equipment capacity if installing the electric energy storage systems and the RPC for use up regenerative power. By using a linear programming, we determined the optimal capacity of the electric energy storage systems and the RPC.